Hubungan Antara Kecemasan Mahasiswa Tingkat Akhir Dengan Efikasi Diri Dalam Pemilihan Karir Masa Depan: (Di Program Studi Bimbingan Dan Konseling Angkatan 2020 Universitas Sanata Dharma Yogyakarta) - Agry Gading Larasati (Institut Nalanda, 2024)
This study aims to determine whether there is a relationship between the anxiety of final year students and self-efficacy in choosing future careers in the class of 2020 at the Guidance and Counseling Study Program of Sanata Dharma University. This study used a correlation test with a sample of 60 respondents consisting of final year students at Sanata Dharma University, Guidance and Counseling Study Program. The data analysis techniques used are categorization, normality test, linearity test, and correlational hypothesis test. Data were collected using an anxiety scale with a valid item count of 34 with a reliability test value of 0.886 and a self-efficacy scale with a valid item count of 21 and a reliability value of 0.912.The results in this study prove: There is no relationship between the anxiety of final year students and self-efficacy in choosing a future career in the Guidance and Counseling Study Program of Sanata Dharma University.